2019
DOI: 10.1557/adv.2019.262
|View full text |Cite
|
Sign up to set email alerts
|

Improving the Time Stability of Superconducting Planar Resonators

Abstract: Quantum computers are close to become a practical technology. Solid-state implementations based, for example, on superconducting devices strongly rely on the quality of the constituent materials. In this work, we fabricate and characterize superconducting planar resonators in the microwave range, made from aluminum films on silicon substrates. We study two samples, one of which is unprocessed and the other cleaned with a hydrofluoric acid bath and by heating at 880 in high vacuum. We verify the efficacy of the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…This is particularly relevant to qubit-qubit coupling calibration, which cannot be performed in parallel on all qubits. Second, TLS defects in the environment are known to fluctuate over time [31,33,41,42]. Similarly, f q itself can shift in time.…”
Section: Qubit Calibration In Frequency-tunable Architecturesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly relevant to qubit-qubit coupling calibration, which cannot be performed in parallel on all qubits. Second, TLS defects in the environment are known to fluctuate over time [31,33,41,42]. Similarly, f q itself can shift in time.…”
Section: Qubit Calibration In Frequency-tunable Architecturesmentioning
confidence: 99%
“…Despite these successes, the high-fidelity operation of medium-and large-scale quantum computers is accompanied by the daunting task of calibrating numerous physical qubits. In particular, calibrating tunable qubits requires the estimation of resonant interaction parameters such as the resonance frequency and coupling coefficient between pairs of interacting qubits [27,28], a qubit and a resonator [18], two-level state (TLS) defects [29][30][31], or substrate and box modes [32]. These calibrations are necessary to implement two-qubit gates and avoid loss of quantum information due to spurious interactions leading to coherent or incoherent errors.…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that driving resonators electrically saturates TLSs, leading to a higher Q r int [9]; this can also be accomplished via an off-resonant drive [13][14][15]. The effect of TLSs is not limited to loss mechanisms but also leads to noise (i.e., time fluctuations) in Q r int and in the resonator resonance frequency f r [16][17][18]; qubits exhibit an equivalent behavior [12,[19][20][21][22][23]. Our main motivation is to gain a deeper insight into the physics of TLS-induced time fluctuations for much longer time periods and a wider range of parameters compared to these previous works.…”
Section: Introductionmentioning
confidence: 99%
“…A large body of work on CPW resonators and qubits has shown that TLSs are likely hosted in native oxide layers [8][9][10][11][12][13][14][15][16][17] at the substrate-metal (SM), substrateair (SA), or metal-air (MA) interfaces [4,[18][19][20]. TLSs originate within these layers because naturally occurring oxides deviate from crystalline order.…”
Section: Introductionmentioning
confidence: 99%
“…Superconducting quantum devices interact (semi-)resonantly with Q-TLSs [21], affecting the internal quality factor of resonators, Q i , or the energy relaxation time of qubits, T 1 . Several authors have hypothesized that Q-TLSs additionally interact with T-TLSs [22][23][24], leading to experimentally observed stochastic fluctuations in Q i and f r [15,16,22,25] as well as T 1 and f q [2,26]. The model proposed by these authors depart from the TLS standard tunneling model (STM), where TLS interactions are neglected [3].…”
Section: Introductionmentioning
confidence: 99%